2013
DOI: 10.1186/1556-276x-8-496
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity of different-sized ZnO nanoparticles in Caco-2 cells

Abstract: There has been rapid growth in nanotechnology in both the public and private sectors worldwide, but concern about nanosafety exists. To assess size-dependent cytotoxicity on human cancer cells, we studied the cytotoxic effect of three kinds of zinc oxide nanoparticles (ZnO NPs) on human epithelial colorectal adenocarcinoma (Caco-2) cells. Nanoparticles were first characterized by size, distribution, and intensity. Multiple assays have been adopted to measure the cell activity and oxidative stress. The cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 25 publications
5
91
0
1
Order By: Relevance
“…However, Kang et al found that cytotoxicity exhibited doseand time-dependent effects for ZnO NPs. It was observed the cell activity is significant different between the concentration of 0.0125 and 0.050 g/L for 24 h against Caco-2 cells (Kang Guan et al 2013). Sharma et al found that ZnO NPs (0.008-0.02 g/L) can reduce the human epidermal cell (A431) viability for 24 and 48 h in a concentration and time dependent manner (Sharma, Shukla et al 2009).…”
Section: Introductionmentioning
confidence: 97%
“…However, Kang et al found that cytotoxicity exhibited doseand time-dependent effects for ZnO NPs. It was observed the cell activity is significant different between the concentration of 0.0125 and 0.050 g/L for 24 h against Caco-2 cells (Kang Guan et al 2013). Sharma et al found that ZnO NPs (0.008-0.02 g/L) can reduce the human epidermal cell (A431) viability for 24 and 48 h in a concentration and time dependent manner (Sharma, Shukla et al 2009).…”
Section: Introductionmentioning
confidence: 97%
“…These discrepancies could derive from the loss of functions that secondary cell cultures must inevitably encounter, due to genomic alterations or as a result of repeated passages in culture, which is likely to select cells with a particular culture-conditioned biochemical phenotype. However, it should be noted that, a correlation between the response obtained by using primary and immortalised cells has been observed in some situations, including studies testing NPs with a well-known grade of cytotoxic activity, i.e., Ag NPs and Zn NPs (68)(69)(70)(71)(72)(73)(74).…”
Section: In Vitro Systems: Primary Cells Vs Immortalised Cellsmentioning
confidence: 99%
“…ZnO nanoparticles produce cytotoxic effects in numerous kinds of cells, including osteoblast cancer cells, human bronchial epithelial cells, kidney cells, alveolar adenocarcinoma cells, hepatocytes, and embryonic kidney cells; furthermore, the nanoparticles' effects may be related to particle size and dosage [18,19].…”
Section: Introductionmentioning
confidence: 99%